2004
DOI: 10.1007/s00595-003-2738-5
|View full text |Cite
|
Sign up to set email alerts
|

Operative Morbidity Associated with Groin Dissections

Abstract: S-shaped incisions more often resulted in lymphatic collection and stagnation, with a higher incidence of wound infections and leg edema than straight incisions. Therefore, we now perform straight incisions to minimize the risk of wound infections and leg edema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(33 citation statements)
references
References 16 publications
2
30
0
1
Order By: Relevance
“…49 Furthermore, wound complications after IL represent a significant cost to the health care system as they require prolonged wound care, which may sometimes require hospital re-admission and, in the case of extensive dehiscence/necrosis with exposure of the femoral vessels, return to the operating room for skin grafting or muscle transposition. 49,50 With the aim of prevention or minimization of postoperative morbidity after IL, several modifications to the original technique have been suggested. Techniques that limit the length or vary the type of incision (straight oblique incision, 6 double incision, 11 minimal access incisions 26 ) and other technical variants, including preservation of the saphenous vein, preservation of the muscle fascia, sartorious muscle transposition or omental flap 51 have been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…49 Furthermore, wound complications after IL represent a significant cost to the health care system as they require prolonged wound care, which may sometimes require hospital re-admission and, in the case of extensive dehiscence/necrosis with exposure of the femoral vessels, return to the operating room for skin grafting or muscle transposition. 49,50 With the aim of prevention or minimization of postoperative morbidity after IL, several modifications to the original technique have been suggested. Techniques that limit the length or vary the type of incision (straight oblique incision, 6 double incision, 11 minimal access incisions 26 ) and other technical variants, including preservation of the saphenous vein, preservation of the muscle fascia, sartorious muscle transposition or omental flap 51 have been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…However, the procedure has often been associated with high morbidity and prolonged hospital stay. Tonouchi et al (16) reported an overall wound infection rate of 24% and an incidence of moderate to severe infection of 16%. Compared with straight incisions, an S-shaped cutaneous incision seems to influence the incidence of volume of drain discharge.…”
Section: Discussionmentioning
confidence: 98%
“…Two other factors that contribute to wound complications are obesity and aging. Leg edema occurs in 40% of patients; pulmonary embolism has been reported in 0.6%-1.0% (16).…”
Section: Discussionmentioning
confidence: 99%
“…This straight oblique incision is superior to the straight vertical and S-shaped ("hockey stick") incisions, which are associated with an increased rate of postoperative complications (21) . Superficial inguinal lymph nodes in the previously described distribution are removed en bloc.…”
Section: Surgical Approach Historical Prospectivementioning
confidence: 97%